Clinico-Pathology and Surgical Management of Leiomyosarcoma in Dog: A Case Report - Khandelwal, Priya; Singh Gurjar, Kuldeep; Mishra, Rakesh; Rathore, Annu; Kumar, Naveen (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A malignant smooth muscle tumour of mesenchymal  origin, leiomyosarcoma can develop anywhere in the  body. Smooth muscle is the site of this slow-growing, locally  invasive, malignant tumour, which usually spreads slowly.  Deep dermal smooth muscle, arrector pili, or vascular  areas in the genital region can all give birth to dermal  smooth muscle tumours (Enzinger et al., 2001). They are  identified as angioleiomyomas and angio-leiomyosarcomas,  pilo-leiomyomas and pilo-leiomyosarcomas, or genital  leiomyomas and leiomyosarcomas, respectively (Liu and  Mikaelian, 2003). Dermal smooth muscle tumours occur most  frequently in dogs, cats and ferrets (Bahl et al., 2020). Surgical  resection is the treatment most used for leiomyosarcoma.  In humans and most other animals, leiomyosarcomas are  relatively common in the visceral organs, especially the  gastrointestinal tract and female genital tract, and in the  spleen in dogs (Enzinger et al., 2001; Cooper and Valentine,  2002). Leiomyosarcoma rarely occurs in other organs; only  a few cases in the oral cavity, oesophagus, and urinary  bladder have been reported in humans and animals (Enzinger  et al., 2001; Cooper and Valentine, 2002). Subcutaneous  leiomyosarcoma is extremely rare in animals. This document  puts on record a clinico-pathological study and surgical  management of leiomyosarcoma in a dog.
Keywords: surgery; origin; leiomyosarcoma; develop; haemoglobin